Reliable suzuki chemistry for functionalised polythiophene synthesis - Higgins,SJ; Liversedge,I; Badriya,S; Heeney,M; Giles,M; McCulloch,L (2007)
Until recently, the synthesis of polythiophenes using Suzuki chemistry has proven difficult because of the ready protodeborylation of thiophene boronates. However, we now report that the new generation of bulky, electron-rich Pd(O)-phosphane catalysts are effective and reliable for the preparation of regioregular polyalkylthiophenes using Suzuki coupling. Moreover, the monomers can be prepared in high yield by Ir-catalysed borylation, without the need for strong organolithium bases, making this potentially a highly functional group-tolerant approach to polyalkylthiophene derivatives. Perfluoroalkylthiophenes also undergo this reaction. Copyright © 2007 Materials Research Society.